PEMBERDAYAAN EKONOMI IBU-IBU PKK MELALUI PEMBUATAN LILIN AROMATERAPI DARI MINYAK JELANTAH DI BANJAR TEGAL ASAH DESA SANUR - Eka Rahma Tirani; Allya Zahra Santoso; Aisyah Nur Vinani; Istamala Idha Retnoningsih; I Komang Sukendra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service program was initiated in response to environmental concerns related to improper disposal of household used cooking oil and the lack of eco-based entrepreneurial skills among residents. The situation was observed in Banjar Tegal Asah, Denpasar, where local housewives lacked access to environmentally friendly skill training. As a solution, a hands-on training in making aromatherapy candles from used cooking oil was conducted using a participatory approach. Participants learned the process of filtering, purifying, mixing ingredients, molding, and packaging. The results indicated an increase in ecological awareness, technical skills, and entrepreneurial interest. This activity demonstrates that household waste can be transformed into valuable products and serve as a sustainable model for women’s home-based empowerment.